Perspectives of black histories in schools - King, LaGarrett J. (Research in social education., 2019)
"Concerned scholars and educators, since the early 20th century, have asked questions regarding the viability of Black history in k-12 schools. Over the years, we have seen k-12 Black history expand as an academic subject, which has altered research questions that deviate from whether Black history is important to know to what type of Black history knowledge and pedagogies should be cultivated in classrooms in order to present a more holistic understanding of the group's historical significance. Research around this subject has been stagnated, typically focusing on the subject's tokenism and problematic status within education. We know little of the state of k-12 Black history education and the different perspectives that Black history encompasses. The book, Perspective of Black history in schools, brings together a diverse group of scholars who discuss how k-12 Black history is understood in education. The book's chapters focus on the question, what is Black history, and explores that inquiry through various mediums including its foundation, curriculum, pedagogy, policy, and psychology. The book provides researchers, teacher educators, and historians an examination into how much k-12 Black history has come and yet how long it still needed to go"--